High-accuracy fluence determination in ion beams using fluorescent nuclear track detectors - Osinga-Blättermann, Julia-Maria; Akselrod, M. S.; Herrmann, R.; Hable, V.; Dollinger, G.; Jäkel, Oliver; Greilich, Steffen (Radiation measurements, 2013)
We present an approach to use Al2O3:C,Mg-based fluorescent nuclear track detectors (FNTDs) and confocal laser scanning microscopy as a semiautomatic tool for fluence measurements in clinical ion beams. The method was found to cover a linear energy transfer (LET) range from at least L∞(Al2O3) = 0.5 keV/μm to 61,000 keV/μm with a detection efficiency ≥99.83% (20 MeV protons) at particle fluences up to at least 5 × 107 per cm2. Our technique allows to determine the spatial fluence distribution on a microscopic scale and enables detailed track-by-track comparison studies between different fluence detectors.